Oral dexamethasone decreases postoperative pain, swelling, and trismus more than diclofenac following third molar removal: a randomized controlled clinical trial - Lima, Carlos Alysson Aragão; Favarini, Vinícius Tatsumoto; Torres, Alexandre Machado; da Silva, Rogério Almeida; Sato, Fábio Ricardo Loureiro [UNESP] (Springer Nature, 2017)
Purpose: The aim of this study was to compare the anti-inflammatory potential of two pharmacotherapy protocols based on the parameters of pain, trismus, and swelling, after extraction of third molars. Methods: Thirty patients selected with symmetrical impaction of third molars were submitted to surgical procedures in both sides in different times. For one group, dexamethasone was used for 3 days, and for another group diclofenac sodium was also used for the same period. The main variables analyzed were the visual analogue pain scale (VAS), but others were also analyzed such as swelling and trismus, which were submitted to statistical analysis. Results: The results had no difference regarding the length of procedures (p = 0.986) and the pain in the immediate and 4-h postoperative period (p = 0.723 and 0.541). The rescue analgesic consumption was higher (p < 0.05) when using the protocol with diclofenac sodium. The variables mouth opening (p < 0.05) and swelling (p < 0.05) were significantly better when using the protocol with dexamethasone in the postoperative period. Conclusions: Medical protocol with the use of dexamethasone in the postoperative period was more effective in controlling pain, trismus, and swelling, after the extraction of third molars, when compared to diclofenac sodium.
Keywords: Corticosteroids; Pain; Swelling; Third molar surgery; Trismus